Paisana: A new genus of Neotropical Rhyparochromidae (Hemiptera: Heteroptera: Lygaeoidea) to accommodate Neopamera brachialis (Stål) and four new species - Dellapé, Pablo Matías (Zootaxa, 2008)
A new genus Paisana is erected to accommodate Neopamera brachialis (Stål), and four new Neotropical species: Paisana pampeana from Argentina, Paisana lydiae from Brazil, Paisana maculata from Argentina and Brazil, and Paisana saopaulensis from Brazil. P. brachialis (n. comb.) known only from Brazil is redescribed and recorded for the first time from Argentina. Phylogenetic affinities of this new genus are discussed. Dorsal photographs of the species, illustrations of male genitalia, and a key to the species are provided.